The Islamic embrace of advertising: a study of TV advertising frameworks of selected OIC countries using the hierarchy of influences model - Mokhtar, Aida; Tharmalingam, Selvarajah; Samsudin, Sofiah (2017)
When Islam and life are intertwined for Muslims who are guided by the Islamic principle ‘enjoining good and forbidding evil’, the inculcation of Islamic values in the production of advertising messages for the Muslim audience is crucial. According to some previous studies, Islamic values are absent in some advertisements to Muslims, thus contributing to their inappropriate orientation from the Islamic perspective. The study addresses this by producing a television advertising framework imbued with Islamic principles. For this to happen, the advertising frameworks of selected countries that are members of the Organisation of Islamic Cooperation (OIC) serving as a collective voice for Muslims and working towards a common Islamic market, are examined in this study. The hierarchy of influences model used as the study’s theoretical framework explains the involvement of several factors that contribute to the production of media messages in the form of the nation’s social system, social institutions, organizations, routines and individuals. It is hoped that the significant contributions of this study are to current literature and the development of a television advertising framework that does not contradict with Islamic principles.